Nutritive value of rubber seed (Hevea brasiliensis) meal and oil. II. Rubber seed oil versus corn oil in semipurified diets for rats. - Babatunde Gabriel M; Pond Wilson G
Two experiments were conducted to compare the responses of female weanling rats to 15;protein semipurified diets containing different levels and combinations of rubber seed oil (RSO) and corn oil (CO). The first experiment was a 2x3 factorial arrangement of treatments with two sources of oil, RSO and CO and three levels of oils, 3;, 6;and 9;. The second experiment a composed of five treatments developed to provide 0, 4, 8, 12, and 16;RSO combined with 16, 12, 8, 4, and 0;CO. Each experiment lasted 21 days and all rats were caged individually and fed and watered ad libitium. In Exp. 1, rats fed RSO diets consumed significantly less feed and had lower feed:gain ratio and higher protein efficiency ratio (PER) than those fed the CO diets (P<0.01). There were no significant differrences among the treatments and no interactions due to source or level of oil for the daily gains, organ weights and the hematological traits. In Exp. 2, there were no significant differences among the treatments for any of the variables examined (P>0.05).
Keywords: Chemical composition; Corn oil; Nutritive value; Rat diets; Rubber seed meal; Rubber seed oil